Randomized phase III study of daratumumab versus bortezomib plus daratumumab as maintenance therapy after D-MPB for transplant-ineligible patients with untreated multiple myeloma (JCOG1911, B-DASH study). (27th December 2022) - Suzuki, Tomotaka; Terada, Mitsumi; Machida, Ryunosuke; Kataoka, Tomoko; Ito, Yuta; Kataoka, Keisuke; Maruyama, Dai; Nagai, Hirokazu
Abstract: Daratumumab, melphalan, prednisolone and bortezomib followed by daratumumab maintenance is a standard regimen for transplant-ineligible newly diagnosed multiple myeloma. A large-scale clinical trial demonstrated that progression-free survival declined more sharply during the maintenance phase than during the daratumumab, melphalan, prednisolone and bortezomib induction phase, which suggests the necessity of reinforcing maintenance therapy. This randomized phase III trial aims to confirm the superiority of daratumumab plus bortezomib to daratumumab as maintenance therapy in terms of progression-free survival for transplant-ineligible newly diagnosed multiple myeloma (JCOG1911, B-DASH). First registration (222 patients, within 5 years) was before daratumumab, melphalan, prednisolone and bortezomib administration; those who responded to daratumumab, melphalan, prednisolone and bortezomib were included in the second registration. They were randomized to the daratumumab or daratumumab plus bortezomib maintenance arm. This trial is registered in the Japan Registry for Clinical Trials as jRCT031200320 (https://jrct.niph.go.jp/ ). An ancillary study examining the association of genetic alterations in myeloma cells with prognosis and drug resistance, using next-generation sequencing, is ongoing. Abstract : This phase III trial aims to confirm the superiority of daratumumab plus bortezomib-maintenance over daratumumab-maintenance therapy after daratumumab, melphalan, prednisolone and bortezomib, for transplant-ineligible newly diagnosed multiple myeloma.